Factors related to the decision to receive dental services of pregnant women at Thanyaburi Hospital, Prathum Thani Province - Pangjun , Waraporn (Health Science, Science and Technology Reviews, 2025)
The objective of this study, “Factors Related to the Decision to Receive Dental Services of Pregnant Women at Thanyaburi Hospital, Prathum Thani Province,” is to examine the factors associated with the decision to seek dental care among pregnant women attending antenatal care at Thanyaburi Hospital, Pathum Thani Province. It is a cross-sectional descriptive study conducted with a sample of 269 pregnant women aged 18 years and older, calculated using a logistic regression analysis formula. The research tool is a questionnaire developed from a literature review, consisting of four parts: 1) personal factors, 2) health factors, 3) service factors, and 4) decision to seek dental care. Data was analyzed using multiple logistic regression to present odds ratios and 95% confidence intervals (CI), with statistical significance set at 0.05. The study results revealed three factors significantly associated with pregnant women’s decisions to seek dental services: 1) age: pregnant women aged 30 years and older were 2.546 times more likely to seek dental services than those under 30 (Adjusted OR = 2.546, 95% CI = 1.355 - 4.782, p = 0.004), 2) beliefs/attitudes about oral health: those with high-level beliefs and attitudes about oral health were 3.358 times more likely to seek dental services compared to those with low-level beliefs (Adjusted OR = 3.358, 95% CI = 1.715 - 6.574, p < 0.001), and 3) anxiety about dental treatment: pregnant women with low-level anxiety about dental treatment were 8.463 times more likely to seek dental services than those with high-level anxiety (Adjusted OR = 8.463, 95% CI = 2.141 - 33.455, p = 0.002).